Analisis Tipologi Wilayah Berdasarkan Pertumbuhan Ekonomi, Sektor Basis Dan Disparitas Pendapatan - Fajar Afandi; Aisah Jumiati; Moh. Adenan (Gorontalo Development Review, 2019)
Success Economic development in developing countries can be measured by high economic growth and income distribution. Many economic growth approaches are carried out in several regions in developing regional economic sectors which are expected to increase equity. The research methodology used is descriptive quantitative which explains the results of the calculation to see the condition of the area under study. The purpose of this paper is to determine the condition of regencies / cities in East Java Province based on economic growth, sector basis and the number of income disparities. Based on the results of the study showed that East Java Province was dominated by the quadrant IV category based on the Agriculture sector with a high rate of income disparity.